Le corps et la corde - Olivia Kindl (Ateliers d'Anthropologie)
The amarrada rite of the Peyoteros, performed in the context of the pilgrimage to Wirikuta by the Wixaritari (Huichol) of western Mexico, goes almost unnoticed in specialized studies. Yet it offers us a classic case of a rite of passage, a process limpidly materialized by a rope. Two principal actions are carried out with this ritual instrument: entwining and measuring. They reveal how links are concretely woven between the body, cosmos and individual. Engagement in the Huichol social organisation is also highlighted through the ritual uses of ropes, enabling community links to be tightened. The gestures carried out with these ropes turn out to be crucial, especially for connecting these itinerant bodies to the world, according to specific spatial coordinates and temporal reference points. The transformation of bodies is therefore made possible by concrete ritual processes that use of ropes, causing transformations in social status, alterations in perspective and changes of scale—so many aspects that lead to more general anthropological questions concerning the ritual memory of bodies in movement and a certain ritualized praxis of bodies.